2022
DOI: 10.31015/jaefs.2022.3.12
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and evaluation of the antimicrobial activities of silver nanoparticles from Cyclotrichium origanifolium L.

Abstract: Cyclotricium origanifolium is a plant belonging to the Lamiaceae family and is a species that grows in the Western and Southern Anatolian regions of Turkey. In our study, the antimicrobial activities of silver nanoparticles (AgNP) were investigated through Cyclotricium origanifolium plant extract. Characterization processes of the obtained AgNPs, suitable spectral analysis methods; Uv-Vis was determined by FT-IR, SEM-EDX, XRD. According to the results of the analysis, it was determined that the AgNPs were sphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The band at 453 nm, which is thought to be caused by d-d transitions of the Ag + ion, fully vanished following the green synthesis method. This absence demonstrated that the Ag + cation was fully diminished [ 20 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The band at 453 nm, which is thought to be caused by d-d transitions of the Ag + ion, fully vanished following the green synthesis method. This absence demonstrated that the Ag + cation was fully diminished [ 20 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The mixture's pH was adjusted to 7.0 by adding 1 N sodium hydroxide solution. The maximum absorbance of the produced ST-Ag NPs was measured using a spectrophotometer (Agilent CARY 60) between 300 and 800 nm [ 20 , 23 ]. Transmission electron microscopy (HITACHI 7700), electron dispersive X-ray (Quanta FEG240), field emission scanning electron microscopy (FE-SEM) (Quanta FEG240), atomic force microscopy (AFM), and X-ray diffraction analysis (Rad B-DMAX II) were used to determine the size, surface distribution, morphology, and crystal structure of Ag NPs.…”
Section: Methodsmentioning
confidence: 99%
“…Its mode of action can be associated with various mechanisms such as adhesion to microbial cells, penetration into cells, generation of ROS (reactive oxygen species) and free radicals, or modulation of microbial signal transduction pathways [60,61]. It is known that flavonoids, alkaloids, polyphenols, and terpenoids are the main metabolites used in phytonanoparticle production due to their strong reducing properties [62]. Doulah et al [63] confirmed that A. fimbriopetala, A. linearifolia, A. garandiflora, and A. tubata species growing wild in Iran have a slightly significant effect on fungi.…”
Section: Discussionmentioning
confidence: 99%
“…SeNPs can be generated by physical, chemical and biological (green synthesis) approaches Aktepe et al (2022). Physical and chemical procedures necessitate the use of costly and ecologically hazardous severe poisonous substances (Hatipoglu, 2021;Baran et al 2021).…”
Section: Polat İpekmentioning
confidence: 99%